Sensitivity to Noise Following a Mild Traumatic Brain Injury: A Longitudinal Study. Issue 5 (22nd September 2021) - Shepherd, Daniel; Heinonen-Guzejev, Marja; Heikkilä, Kauko; Landon, Jason; Theadom, Alice
Abstract : Objective: To describe changes in the prevalence and clinical correlates of noise sensitivity (NS) in mild traumatic brain injury (mTBI) across a 12-month period and to determine whether NS at an early stage of recovery has predictive value for later postconcussive symptoms. Setting: A mixed urban and rural region of New Zealand. Participants: Data for 341 adults (201 males, 140 females; age range from 16 to 91 years) were extracted from a 1-year TBI incidence, and outcomes study was conducted in New Zealand. Design: Secondary analysis of data from a community-based, longitudinal population study of an mTBI incidence cohort collected within 1 week of injury (baseline) and at 1, 6, and 12 months postinjury. Main Measures: Measures at baseline (within 2 weeks of the injury) and 1, 6, and 12 months included the Rivermead Post-concussion Symptoms Questionnaire and its NS item, the Hospital Depression and Anxiety Scale, and the computerized CNS-Vital Signs neurocognitive test. Results: NS progressively declined postinjury, from 45% at baseline to 28% at 12 months. In turn, NS showed itself as a significant predictor of future postconcussive symptoms. Conclusion: Taken together with previous research, the findings of the current study indicate that NS may have clinical utility in flagging vulnerability to persistent postconcussive symptoms.